ANALISIS TEORI KEADILAN RESTORATIF TERHADAP DASAR PERTIMBANGAN PUTUSAN HAKIM: KEJAHATAN PENGANCAMAN DI PENGADILAN NEGERI KUPANG (Studi Kasus Putusan Nomor 252/PID.B/2019/PN Kupang) - Petrus De Jenerio Tefa; Reny Rebeka Masu; A Resopijani (Petitum Law Journal, 2026)
This study aims to analyze the application of the theory of restorative justice in the basis for considering judges' sentences for criminal acts of threats based on a case study of Decision Number 252/PID.B/2019/PN Kupang. legally, the regulation of this offense is stipulated in Article 335 Paragraph (1) Points 1 And 2 of the Indonesian Penal Code. This study examines the district court decision of kupang number 252/pid.b/2019/pn kupang, which reveals the presence of a personal vendetta harbored by the victim against the perpetrator prior to the legal incident. This illustrates the potential misuse of legal mechanisms as a means of retaliation in complex interpersonal relationships. Accordingly, this research is guided by the following problem formulations: what are the judicial considerations regarding the crime of threat in decision number 252/pid.b/2019/pn kupang? and how can restorative justice theory be applied in analyzing the judge’s considerations in the aforementioned decision?. This study employs a normative juridical method using statutory, conceptual, and historical approaches. The research findings indicate that in Decision Number 252/Pid.B/2019/PN Kupang, the judge considered both juridical and sociological aspects, namely the fulfillment of the elements of the crime of threat as stipulated in Article 335 paragraph (1) of the Indonesian Penal Code, as well as the social impact of the defendant's actions.